Effects of salinity stress induced by hot spring water on tomato growth, yield and fruit quality under hydroponic cultivation in Japan - Musabyisoni, A.; Mutimawurugo, M. C.; Niyokuri, A. N. (International Journal of Horticultural Science, 2023)
The objective of this research was to test hot spring water as a source of salt to improve tomato quality under the hydroponic system. This research was conducted at Yamagata University, in Japan from February to July 2017. Salt stress was induced using salts of hot spring wastewater collected from Yupoka Onsen (Tsuruoka, Japan). The treatments were EC 2, 4, 8 12, and 16 mS/cm which were arranged in a Randomized Complete Block Design (RCBD) with five replications. Tomato plants were grown at EC 2 until flowering and then subjected to different EC concentrations until harvesting. The data were collected on plant growth parameters and fruit quality. Fruits were harvested at the red stage until the 5th truss. The results showed that fruits' Soluble Solids Content, organic acid, Nitrate contents and Sugar: Acid ratio increased significantly at EC 16 mS/cm and in the upper trusses compared to EC 2 and in the lower trusses. In contrast, fruit weight significantly decreased at EC 16 mS/cm and in upper trusses. Leaf thickness, size and SPAD, and specific leaf weight significantly declined at EC 16 mS/cm and upper leaves compared to EC 2 and in lower leaves. Plant height started to decline significantly after three weeks of treatment at EC 16 compared to EC 2.